1984
DOI: 10.1161/01.str.15.4.736
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral hypoglossal nerve palsy caused by lateral position of the external carotid artery and an abnormally high position of bifurcation of the external and internal carotid arteries--a case report.

Abstract: SUMMARY An unusual case of peripheral hypoglossal nerve palsy, caused by lateral position of the external carotid artery and an abnormally high carotid bifurcation is reported. Improvement followed ligation and cutting of the external carotid artery at its origin. Stroke Vol 15, No 4, 1984 VARIATIONS AND ANOMALIES are common at the bifurcation of the external and internal carotid arteries.1 Lateral position of the external carotid artery 2 " 6 formerly considered extremely rare, has recently been found to b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

1990
1990
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 7 publications
3
15
0
Order By: Relevance
“…Ergür & I˙cke found that the incidence of the subjects with the LP-ECA was %3.5. Ueda et al (1984) reported that the incidence of the LP-ECA was 7.9% on right side, 2.3% on left side and 1% on both sides. In our study, the incidence was 5.5%, 11 subjects with the LP-ECA (8 women, 3 men).…”
Section: Discussionmentioning
confidence: 97%
“…Ergür & I˙cke found that the incidence of the subjects with the LP-ECA was %3.5. Ueda et al (1984) reported that the incidence of the LP-ECA was 7.9% on right side, 2.3% on left side and 1% on both sides. In our study, the incidence was 5.5%, 11 subjects with the LP-ECA (8 women, 3 men).…”
Section: Discussionmentioning
confidence: 97%
“…Thus, to localize a precise lesion in a particular site in the peripheral nerve becomes an important issue in the clinical differential diagnosis [Afi fi et al, 1984]. Although different types of hypoglossal neuropathy are known to cause the deviation of the tongue, it is often diffi cult to distinguish an intracranial lesion from an extracranial one [Ignelzi and Bucy, 1967;Olivier et al, 1977;Ueda et al, 1984;Lieschke et al, 1988;Stankiewicz and Pazevic, 1988]. The present study also has shown that a sizeable number of unmyelinated sympathetic fi bers from the SCG are distributed with the motor fi bers in the hypoglossal nerve.…”
Section: Clinical Correlation Of Sympathetic Component In the Hypoglomentioning
confidence: 99%
“…There have been several reports on rare anatomical variations of the cervical carotid artery (1)(2)(3)(4)(5). These abnormalities were considered to be congenital and to develop during angiogenesis (6, 7); furthermore, they have been considered to be incidental and were not known to cause stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Several anatomical variations of the cervical carotid artery have been found, especially in the carotid bifurcation (1)(2)(3)(4)(5). However, these variations have been considered as cervical carotid artery anomalies and have not implicated in ischemic or hemorrhagic stroke.…”
Section: Introductionmentioning
confidence: 99%